TRADES, MILITIAS AND BROTHERHOODS. ECONOMIC SUCCESS AND PRESTIGE OF THE AFRO- AMERICANS IN SANTIAGO DE CHILE 1780-1820. - Contreras Cruces, Hugo (Revista de Historia Social y de las Mentalidades, 2024)
This paper studies a group of Mulattoes and  other Afro Americans in Santiago de Chile,  during the last years of the eighteenth and early  nineteenth century, who through the practice  of a craft or a retail business and institutional  insertion in caste militias and fraternities began  and solidified a process that, on one hand,  resulted in the accumulation of goods that had  a material and symbolic character , and, on the  other hand, the increase of personal and social  prestige increasingly led them away from the  popular colonial sectors.
Keywords: Artisans; Militants; Brother; Brother Social mobility; Social mobility